Drosophila actin-Capping Protein limits JNK activation by the Src proto-oncogene. - Fernández, B.G.; Jezowska, B.; Janody, F. (Oncogene, 2014)
The Src family kinases c-Src, and its downstream effectors, the Rho family of small GTPases RhoA and Jun N-terminal kinase (JNK) have a significant role in tumorigenesis. In this report, using the Drosophila wing disc epithelium as a model system, we demonstrate that the actin-Capping Protein (CP) ?? heterodimer, which regulates actin filament (F-actin) polymerization, limits Src-induced apoptosis or tissue overgrowth by restricting JNK activation. We show that overexpressing Src64B drives JNK-independent loss of epithelial integrity and JNK-dependent apoptosis via Btk29A, p120ctn and Rho1. However, when cells are kept alive with the Caspase inhibitor P35, JNK acts as a potent inducer of proliferation via activation of the Yorkie oncogene. Reducing CP levels direct apoptosis of overgrowing Src64B-overexpressing tissues. Conversely, overexpressing capping protein inhibits Src64B and Rho1, but not Rac1-induced JNK signaling. CP requires the actin-binding domain of the ?-subunit to limit Src64B-induced apoptosis, arguing that the control of F-actin mediates this effect. In turn, JNK directs F-actin accumulation. Moreover, overexpressing capping protein also prevents apoptosis induced by ectopic JNK expression. Our data are consistent with a model in which the control of F-actin by CP limits Src-induced apoptosis or tissue overgrowth by acting downstream of Btk29A, p120ctn and Rho1, but upstream of JNK. In turn, JNK may counteract the effect of CP on F-actin, providing a positive feedback, which amplifies JNK activation. We propose that cytoskeletal changes triggered by misregulation of F-actin modulators may have a significant role in Src-mediated malignant phenotypes during the early stages of cellular transformation.